Women’s Embodiment and Performance of Masculinity in Nepali Short Stories - Thapa, Bal Bahadur (SCHOLARS: Journal of Arts & Humanities, 2025)
This article examines the representation of the females with masculine features in the Nepali short stories through the analysis of the selected Nepali short stories: Prema Shah’s “Panhelo Gulaf” [“The Yellow Rose”], Padmavati Singh’s “Mauna Swikriti” [“The Silent Consent”], Kumar Nepal’s “Maiyasaheb’s Dayari” [“Maiyasaheb’s Diary”], and Mani Lohani’s “Nirbastra Ira” [“Stripped Ira”]. Despite stigma as well as taboo attached to female body in the Nepali society, the female characters honestly express their bodily experiences, such as love, sex, pregnancy, breastfeeding, menstruation and ovulation. Going beyond the conventional ways of representing the Nepali women, these stories present the Nepali women with masculine characteristics like gazing at males, expressing their desire for sex, asserting their freedom, and resorting to revenge, among others. Engaging with Laura Mulvey’s notion of gendered gaze, Judith Butler’s notion of gender performativity, and Holin Fern Haber’s idea of putting together familiar images in an unfamiliar way, the article claims that the women, as represented in these stories, appropriate, embody and perform masculine gestures, desires and bodies to become subjects and thereby gain agency and bring change. In the context of the present Nepali society, the current study expects to open a new avenue of research to look into the women who embody and perform masculine features in terms of class, caste, ethnicity, religion, and region, among others.